FOXP in Tetrapoda: Intrinsically Disordered Regions, Short Linear Motifs and their evolutionary significance - Viscardi, Lucas Henriques (Genet Mol Biol, 2017)
The FOXP subfamily is probably the most extensively characterized subfamily of the forkhead superfamily, playing important roles in development and homeostasis in vertebrates. Intrinsically disorder protein regions (IDRs) are protein segments that exhibit multiple physical interactions and play critical roles in various biological processes, including regulation and signaling. IDRs in proteins may play an important role in the evolvability of genetic systems. In this study, we analyzed 77 orthologous FOXP genes/proteins from Tetrapoda, regarding protein disorder content and evolutionary rate. We also predicted the number and type of short linear motifs (SLIMs) in the IDRs. Similar levels of protein disorder (approximately 70%) were found for FOXP1, FOXP2, and FOXP4. However, for FOXP3, which is shorter in length and has a more specific function, the disordered content was lower (30%). Mammals showed higher protein disorders for FOXP1 and FOXP4 than non-mammals. Specific analyses related to linear motifs in the four genes showed also a clear differentiation between FOXPs in mammals and non-mammals. We predicted for the first time the role of IDRs and SLIMs in the FOXP gene family associated with possible adaptive novelties within Tetrapoda. For instance, we found gain and loss of important phosphorylation sites in the Homo sapiens FOXP2 IDR regions, with possible implication for the evolution of human speech.